PROFIL BERPIKIR ALJABAR SISWA SMP KELAS VII DITINJAU DARI KEMAMPUAN BERPIKIR LOGIS - Yuniar Astiyani; Mu'jizatin Fadiana (Jurnal Riset Pembelajaran Matematika, 2021)
Algebraic thinking skills for students are important to improve in mathematics learning. Algebra is also closely related to other branches of mathematics. Because every branch of mathematics uses mathematical symbols. So it can be said that algebra is one of the keys to success in learning mathematics. The purpose of this study was to determine algebraic thinking skills in junior high school students in grade VII in terms of logical thinking skills. this type of research is a qualitative study. The subjects in this study consisted of 3 junior high school students in grade VII, each of whom occupied the abstract operasional stage, the transitional stage and the concrete operational stage which were determined through a logical thinking ability test (TKBL). After finding a subject that corresponds to the stage of logical thinking ability, the subject is given an algebraic thinking test. Data collection using written test collection using written test questions and interviews. The results of this study state that the subject of the abstract operational stage is good in algebraic thinking skills, the transitional skills and the concrete operational stage subject is lacking in algebraic thinking skills.